2013
DOI: 10.1179/1754762813y.0000000035
|View full text |Cite
|
Sign up to set email alerts
|

Differences of radiological artefacts in cochlear implantation in temporal bone and complete head

Abstract: These results indicate that it is not possible reliably to determine the exact intracochlear positions of electrodes using CBCT. Imaging of isolated temporal bones produced significantly greater artefacts than imaging of the whole head. Evaluations of image quality based only on results for isolated temporal bones are not transferable to clinical situations, and should be assessed critically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Several publications have shown its potential in visualisation of cochlear electrodes and its accuracy in comparison to histological examination 11 21 - 23 . Even in CBCT, metal artifacts exist and result in reduced power of determination in medial and apical turn of the cochlear 13 14 . The next steps of development will be automatic analyses of the images and imaging fusion of pre- and postoperative data 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several publications have shown its potential in visualisation of cochlear electrodes and its accuracy in comparison to histological examination 11 21 - 23 . Even in CBCT, metal artifacts exist and result in reduced power of determination in medial and apical turn of the cochlear 13 14 . The next steps of development will be automatic analyses of the images and imaging fusion of pre- and postoperative data 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CBCT has been introduced into ENT imaging with a special focus on visualisation of middle and inner ear implants 6 - 8 . Despite some studies that have focused on possibilities 9 - 12 and limitations 13 14 of this method in comparison to CT, some questions still remain. Can different types of electrodes (modiolar vs. lateral position) also be differentiated not only by impression of the observer, but also reproduced by measurements based on CBCT images?…”
Section: Introductionmentioning
confidence: 99%
“…The images do not enable evaluation of the atraumatic nature of the implantation or the preservation of residual hearing. The recent development of the Cone Beam provides new information, and the advantages of this technique in evaluating cochlear trauma are currently being verified in histological samples and in patients [4,8,9].…”
Section: D Micro-ct Scanmentioning
confidence: 99%
“…The use of cone beam CT (CBCT) in otology has increased during the last years with a lower dose cross-sectional technique for visualising bony structures in the ear 2 providing a better resolution than multislice helical CT for the bone structure with strong density contrast 3 . Several studies reported the reliability to assess the scalar position of electrodes array using CBCT in isolated temporal bones 4 - 8 or whole cadaveric heads 9 , but the possibility to apply these results in a real clinical situation on cochlear implanted patients has not been studied in detail. The scalar position of the electrodes in implanted patients was analysed in a study including precurved and straight arrays implanted in 61 ears 10 but the reliability of the radiological exam was not reported.…”
Section: Introductionmentioning
confidence: 99%